Vascular dysfunction in HFpEF: Potential role in the development, maintenance, and progression of the disease - Saavedra-Alvarez, Andrea; Pereyra, Katherine V.; Toledo, Camilo; Iturriaga, Rodrigo; Del Rio, Rodrigo (Frontiers in Cardiovascular Medicine, 2022)
Heart failure with preserved ejection fraction (HFpEF) is a complex heterogeneous disease characterized by autonomic imbalance, cardiac remodeling, and diastolic dysfunction. One feature that has recently been linked to the pathology is the presence of macrovascular and microvascular dysfunction. Indeed, vascular dysfunction directly affects the functionality of cardiomyocytes, leading to decrease dilatation capacity and increased cell rigidity, being the outcome the progressive decline in myocardial function. The presence of an inflammatory condition in HFpEF produced by an increase of pro-inflammatory molecules and activation of immune cells (i.e. chronic low-grade inflammation) has been proposed to play a pivotal role in vascular remodeling and endothelial cell death, which may ultimately lead to increase the arterial elastance, decrease myocardium perfusion and decrease oxygen supply to the tissue. Despite, the precise mechanism linking low-grade inflammation to vascular alterations in the setting of HFpEF is not completely known. However, enhanced sympathetic vasomotor tone in HFpEF, which may result from inflammatory activation of the sympathetic nervous system, could contribute to orchestrate vascular dysfunction in the setting of HFpEF due to exquisite sympathetic innervation of both the macro and microvasculature. Accordingly, the present brief review aims to discuss main mechanisms that may be involved in the macro and microvascular function impairment in HFpEF and the potential role of the sympathetic nervous system on the vascular dysfunction.